Pelaksanaan Pengembangan Motorik Halus Anak pada Sentra Seni dan Kreativitas di TK - Fitri, Ramadaniah; Hazizah, Nur (Penerbit Aksara Rentaka Siar (ARS), 2019)
This study aims to describe the implementation of fine motor development at TK Pertiwi 3, Office of the Governor of Padang. This research is a qualitative approach with descriptive method. The researcher uses the principal and teacher as informants. Ways to collect data that researchers use are observation, interviews, and documentation. The data analysis technique is done using data triangulation techniques. The results of the fine motor development activities at TK Pertiwi 3 The Office of the Governor of Padang has been carried out well as expected. The implementation of fine motoric development is carried out in the arts center and creativity by way of each class so that children do not feel bored. Every activity of implementing fine motor development is done more emphasized through activities that use hands, fingers through activities that produce a work. The teacher conducts fine motor development by providing simulations with various kinds of activities. The teacher has used a variety of methods in the implementation of the child's fine motor development, namely using, demonstration methods, direct practice methods, and methods of giving assignments.